"Back in the night": reflections, after forty years, on the nature, uses and value of visual ephemera. (5th April 2016) - Pollard, Nik
Abstract : The author gives context to the 1977 article 'Arty choke: acquisition and ephemera', and re-assesses his ideas with the perspective of a long career in librarianship and four decades of involvement with this and other library materials. He argues for a broad definition of ephemera and for art libraries to collect and make accessible as comprehensively as possible all designed visual artifacts potentially pertinent to the study of art history and the practices of art and design.